Comorbidity, Functional Impairment, and Emotional Distress: A Coping Mediation Model for Persons With Cancer. Issue 10 (1st February 2021) - Merluzzi, Thomas V; Philip, Errol J; Gomer, Brenna; Heitzmann Ruhf, Carolyn A; Kim, Dahyeon
Abstract: Background: Comorbid disease in cancer patients can substantially impact medical care, emotional distress, and mortality. However, there is a paucity of research on how coping may affect the relationship between comorbidity and emotional distress. Purpose: The current study investigated whether the relations between comorbidity and emotional distress and between functional impairment and emotional distress were mediated by three types of coping: action planning (AP), support/advice seeking (SAS), and disengagement (DD). Methods: Four hundred and eighty-three persons with cancer completed a measure of functional impairment (Sickness Impact Profile), the Checklist of Comorbid Conditions, the Brief COPE, the Hospital Anxiety and Depression Scale, the Quality of Life Assessment for Cancer Survivors (Negative Feelings Scale), and the Distress Screening Schedule (Emotional Distress Scale). The latter three measures were used to form a latent construct representing the outcome, emotional distress. Results: Model comparison analysis indicated that the model with DD as a mediator had a better fit than models containing AP and SAS. DD mediated the relationship between functional impairment and emotional distress, so that engaging in DD was associated with greater distress. In addition, comorbidity and functional impairment were directly and positively related to emotional distress, but the relation between comorbidity and distress was not mediated by coping type. Conclusions: Both comorbidity and functional impairment may be associated with distress, but disengagement coping only mediated the relation involving functional impairment and was positively associated with distress. Future studies can investigate whether teaching active coping or adaptive coping (e.g., through mindfulness exercises) can decrease distress in cancer patients, despite functional impairments. Abstract : In persons with cancer, having serious comorbid diseases and physical functional impairment was related to emotional distress; in addition, disengagement, the only coping mechanism used for dealing with functional impairment, was also associated with emotional distress.